Challenges in adopting health technology assessment for evidence-based policy in Iran: a qualitative study - Meysam Behzadifar; Saeed Shahabi; Ahad Bakhtiari; Samad Azari; Mohammad Yarahmadi; Mariano Martini; Masoud Behzadifar (Journal of Health, Population and Nutrition)
Abstract Background Health Technology Assessment (HTA) is a vital tool for evidence-based healthcare decision-making, yet its adoption in Iran remains limited despite its potential to improve policy and resource allocation. This qualitative study explores the challenges hindering the integration of HTA into Iran’s healthcare system, providing insights from key stakeholders. Methods A qualitative research design was employed, using in-depth, semi-structured interviews with 23 stakeholders, including health policymakers, HTA experts, and healthcare professionals. Participants were selected through purposive sampling to ensure diverse representation across Iran’s healthcare sectors. Data were analyzed using thematic content analysis based on Braun and Clarke’s framework, with MAXQDA software for coding and analysis. Validation was achieved through member-checking and peer debriefing. Results The challenges were categorized into internal and external factors. Internal factors included institutional challenges such as a lack of clear policies or guidelines, inadequate institutional support, and bureaucratic constraints; resource limitations, including insufficient financial resources, human resource shortages, and gaps in technological infrastructure; knowledge and awareness gaps, characterized by limited awareness among decision-makers, insufficient training and education, and a preference for traditional methods; and data and evidence gaps, including a lack of reliable data, a limited local evidence base, and challenges in data sharing. External factors included political and economic influences, such as political instability, policy shifts, economic pressures, and the influence of interest groups; as well as ethical and equity concerns, which involved challenges in ethical decision-making, equity concerns, and public perception and acceptance. Conclusion This study highlights the multifaceted challenges to HTA adoption in Iran, emphasizing the need for stronger institutional frameworks, increased resources, enhanced stakeholder awareness, and improved public engagement. Addressing these challenges through targeted policy interventions can facilitate the integration of HTA into healthcare decision-making, promoting more equitable and evidence-based policies in Iran. These findings can guide policymakers and healthcare leaders in designing context-specific solutions to enhance HTA utilization. The findings also offer valuable lessons for other low- and middle-income countries facing similar challenges, contributing to the global discourse on HTA implementation in resource-constrained settings.